Educação musical na educação infantil: uma investigação na formação e práticas das professoras - Pacheco, Eduardo Guedes (2005)
This research deals with the possibility of a formation process construction in Musical Education for acting teachers in children education classes. Under the theme Musical Education in Children Education: an investigation-action in the formation and the practice of the teachers , this project had as main objective to investigate the development of pedagogical actions in Musical Education from the constitution of an acting teachers group in children education classes. The specific objectives are presented: a) to problem the conceptions that guide the educational practices of the teachers who act in children education classes and b) to investigate the formation and action process in musical education of these. The methodological pathway was the educational investigation-action. The choice reveals the intention that the work could contribute to the researched reality, proposing an approach by the researcher concerning the investigated situations but also making possible that the teachers, subjects of this investigating process, could participate in the decision taking as investigators of their own practices. The work was carried out in the Ipe Amarelo Child Education Nucleus, located in the campus of Universidade Federal de Santa Maria. Four acting teachers of the children education classes were part of the investigating group. The self-reflexive spiral guided the orientation for the investigation process organization. The planning meetings served the discussions concerning the educational practices planning organization and made possible the creation of musical learning situations for the teachers. In the meetings, reflections about the carried out activities also happened, redirecting their re-planning. During the process it was possible to notice that the teachers were able to overcome the conceptions that were attributed to the musical education, a co-acting role in the educational process. The proposed discussions in this dissertation give evidence to the possibility that through the constitution of an investigation-action group, teachers who act in children education may develop musical education pedagogical actions in this phase of basic education.